Conservative women in contemporary Turkish politics : mobilization, party politics and voting - Kourou, Nur Sinem. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2022., 2022)
This dissertation examines women's political participation process (a.k.a political feminization) in the case of Turkey's AKP. Therefore, it is built on a puzzle between the number of women in the party and the party's gender agenda. It focuses on the political participation process of women through qualitative research on the party's women's branches and party's women voters. By analyzing the relationship, the party's anti-feminist agenda deliberately specifies the limits of women's political involvement bolstering it with the party's Islamist-conservative ideology. Afterwards, without challenging the strict bounds of the party, women activists (actors in the party's women branches) rigorously navigate their political survival by polishing their mobilization abilities. The research findings suggest that AKP reaches out women without pledging to gender equality or feminist emancipation while rhetorically encouraging their participation into politics both as activist and voter. In return, women form their political style considering the limits and pushing the presumable opportunities, which stem from the the limits. Moreover, women voters raise their political agency by routinizing the voting behavior and identifying themselves as the AKP's supporters.
Keywords: Adalet ve Kalkınma Partisi (Turkey); Women -- Political activity -- Turkey.